2009
DOI: 10.1038/nchem.249
|View full text |Cite
|
Sign up to set email alerts
|

Designer magnetic superatoms

Abstract: The quantum states in metal clusters are grouped into bunches of close-lying eigenvalues, termed electronic shells, similar to those of atoms. Filling of the electronic shells with paired electrons results in local minima in energy to give stable species called magic clusters. This led to the realization that selected clusters mimic chemical properties of elemental atoms on the periodic table and can be classified as superatoms. So far the work on superatoms has focused on non-magnetic species. Here we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
225
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(241 citation statements)
references
References 42 publications
6
225
2
1
Order By: Relevance
“…The variations in the intensity in mass spectra are generally attributable to the experimental conditions. As we are primarily interested in the magnetic character and since our previous theoretical studies had identified VNa 8 to be a magnetic superatom, 17 the negative ion photoelectron spectra were collected for the VNa x − clusters containing 6, 7, 8, and 9 Na atoms. These are shown in Figures 2 and 3.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variations in the intensity in mass spectra are generally attributable to the experimental conditions. As we are primarily interested in the magnetic character and since our previous theoretical studies had identified VNa 8 to be a magnetic superatom, 17 the negative ion photoelectron spectra were collected for the VNa x − clusters containing 6, 7, 8, and 9 Na atoms. These are shown in Figures 2 and 3.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Since the 1D-state has a strong component from the atomic d-state of V, it undergoes a large exchange splitting, leading to a cluster with a spin magnetic moment of 5.0 μ B . 17 Until now, there has been no experimental evidence for the formation of such magnetic states and the nature of the associated ground state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au n (SR) m clusters with a wide range of physical and chemical properties can then be produced. 148,149 In the study for high-resolution separation, we separated large magic Au n (SR) m clusters (n > 100) at high resolution by HPLC using reverse-phase columns. This technique is expected to provide a greater understanding of the size dependence of structural and physical properties for magic Au n (SR) m clusters.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Thus, the Li 3 O + cluster contains 8 valence electrons and corresponds to a magic species in accordance with the 18-electron rule 23,24 . Clearly the closed-shell electron structure is classified as a superatom that consists of specific atoms that share electrons but mimics the chemical behavior of other elements [25][26][27][28][29][30] . However, unlike previous reports of magnetic lithium superatoms that were stretched in three dimensions 31 , Li 3 O + possessed a planar structure while maintaining its superatomic properties.…”
mentioning
confidence: 99%